SHAPE AND CLUSTER ANALYSES FOR DISCRIMINATING POPULATIONS OF RHIZOPRIONODON POROSUS OF NORTHEAST COAST OF BRAZIL THROUGH CHONDROCRANIUM MORPHOMETRY - LUCENA, Leandro Ricardo Rodrigues de; LESSA, Rosângela Paula Teixeira (Brazilian Journal of Biometrics, 2019)
The genus Rhizoprionodon comprises seven species of sharks occurring in the Atlantic, Pacific and Indian Oceans. The sharks are small sized attaining about 150 cm, inhabiting coastal waters, estuaries and brackish waters. In Brazil, the two species found are Rhizoprionodon porosus and R. lalandii. The use of morphometric approaches has limitations for this group due to lack of anatomical landmarks, since they have a continuous form without angles. This study will analyze the chondrocranium, a structure that has species-specific shape, aiming at verifying the hypotheses suggested in the literature of two populations of R. porosus off northeastern Brazil. One population corresponds to the northern coast of the Northeast (RN) and, the other to the eastern coast of this region (PE). We performed a comparative morphometric study of the chondrocranium of R. porosus between areas using shape and cluster analyses. The results showed that there were differences for both adult and juvenile phases by areas of capture. In conclusion, there is indeed differences between chondrocrania from Pernambuco and Rio Grande do Norte.